2014
DOI: 10.3851/imp2942
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Lamivudine-Resistance-Associated Vaccine-Escape HBV Mutants among HIV-Coinfected Patients on Prolonged Antiretroviral Therapy

Abstract: Considering this alarmingly high incidence of 3TC-resistant triple mutation and its possible clinical/public health implications, proper management of 3TC-resistance among HIV-HBV-coinfected patients is an urgent necessity in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…This serum marker of active viral replication was accompanied by high serum levels of HBV DNA [22, 40]. We found a similar phenomenon by univariate analysis in our study.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This serum marker of active viral replication was accompanied by high serum levels of HBV DNA [22, 40]. We found a similar phenomenon by univariate analysis in our study.…”
Section: Discussionsupporting
confidence: 78%
“…However, this could not be confirmed by multivariate analysis. The median of CD4+ lymphocyte counts was found to be significantly higher in patients with 3TC-resistant mutations than viraemic HBV patients without these mutations [22]. We also obtained similar results by univariate analysis in our study, although again this could not be confirmed on multivariate analysis.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Three major patterns of mutations in the HBV polymerase associated with lamivudine resistance were described in HBV/HIV co-infected patients receiving ART with lamivudine as the sole-anti-HBV drug: single rtM204V, double rtL180M+rtM204V and triple rtV173L+rtL180M+rtM204V. This triple mutant is related to a vaccine escape mutant due to the corresponding change in the overlapped S-ORF [61]. Thus, the use of lamivudine as the only active anti-HBV agent is discouraged [62].…”
Section: Current Prevalence Of S-escape Mutantsmentioning
confidence: 99%